PERBEDAAN NILAI LEUKOSIT PRA DAN PASCAOPERASI SEBAGAI PREDIKTOR LUARAN FUNGSIONAL PERDARAHAN INTRASEREBRAL SPONTAN - Hanif Gordang Tobing,* Bismo Nugroho PPR,* Mohamad Saekhu,* Setyo Widi Nugroho,* Affan Priyambodo,* (NEURONA, 2019)
INTRODUCTION HEMATOMA IN SPONTANEOUS INTRACEREBRAL HEMORRHAGE SICH RESULTS INFLAMMATION DUE TO SECONDARY BRAIN INJURY LEUKOCYTE AN INFLAMMATION INDICATOR WHICH IS ROUTINELY EXAMINED KNOWN AS AN OUTCOME PREDICTOR IN NON OPERATED SICH THE ROLE OF INFLAMMATION IN OPERATED SICH IS STILL UNKNOWN HOWEVER PRE AND POSTSURGERY LEUKOCYTE COUNTS CAN BE A MARKER OF BRAIN TISSUE DAMAGE BRAIN INJURY